Genetic connectivity in Twospot flounder (Bothus robinsi) across the Gulf of Mexico, inferred with single nucleotide polymorphisms from larvae and adults - Morales-Pulido, José Manuel; Munguia-Vega, Adrian; Jiménez-Rosenberg, Sylvia Patricia A.; Rocha-Olivares, Axayacatl; Galindo-Sánchez, Clara E. (Frontiers in Marine Science, 2023)
Larval genetic information influences populations’ genetic pools, causing genetic homogenization or structuration. So, knowing about adult and larval genetic information is essential to understand processes such as connectivity. The aims are to evaluate Twospot flounder (Bothus robinsi, a fish with a high dispersal potential) larval pools’ genetic diversity, test if the larvae tend to mix or display collective dispersal, compare genetic information between larvae and adults and evaluate its connectivity. We used ddRADSEQ to genotype 1,034 single nucleotide polymorphic sites from B. robinsi larvae sampled in waters from the Bay of Campeche and the eastern Gulf of Mexico (GOM) and adults sampled on Florida’s continental shelf. Larvae were identified morphologically and by DNA barcoding. We estimated Fst-paired comparations, Principal Components Analysis (PCA), Discriminant Analyses of Principal Components (DAPC), and a Structure analysis to understand genetic trends. With the software COLONY, we made a sibship evaluation. We observed no significant heterogeneity among regions (Fst p-values>0.05). PCA, DAPC, and the Structure Analysis showed one genetic cluster, indicating genetic homogeneity. We did not detect full-sibs or half-sibs. We linked the results with the high dispersal potential of B. robinsi due to a long pelagic larval duration and the potential of ocean dynamics to transport and mix larvae from all GOM shelf areas. These findings suggest that the dispersal potential of B. robinsi is large enough to produce genetic connectivity in all GOM subpopulations and that time spent by its larvae in dispersal pathways is enough to mix larvae from different GOM subpopulations, indicating a panmictic population.